Identifying new safety risk of human serum albumin: a retrospective study of real-world data - Lu, Hui; Zhang, Yuwei; Liu, Pengcheng (Frontiers in Pharmacology, 2024)
Objective To mine and analyze the adverse reaction signals of human serum albumin (HSA) using the FDA adverse event reporting system (FAERS) database for the safe clinical use of this drug.Methods Data cleaning and analysis of adverse event reports in the FAERS database for a total of 76 quarters from Q1 2004 to Q4 2022 were performed using the reporting odds ratio (ROR), Medicines and Healthcare Products Regulatory Agency (MHRA), and Bayesian confidence propagation neural network (BCPNN). Gender-differentiated signal detection was used to investigate the gender differences in the occurrence of HSA adverse events.Results Through a combination of three methods, a total of 535 adverse event reports were identified. These reports involved 1,885 cases of adverse reactions, with respiratory, thoracic, and mediastinal disorders, as well as general disorders and administration site conditions, as the most common. One noteworthy new signal was the occurrence of transfusion-related acute lung injury. Additionally, gender-differentiated signals were present, with females experiencing paraesthesia, hypertension, pulmonary oedema, loss of consciousness, and vomiting.This study has revealed that HSA poses a risk of causing transfusion-related acute lung injury. It has also been observed that adverse reactions, including paraesthesia, hypertension, pulmonary oedema, loss of consciousness, and vomiting, are more prevalent in females. These findings should be taken into account when using HSA in a clinical setting.